(3JYOjd GdeYjGQ aj fbO JfRjd GdCPcGQs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s ((3eMeO Hf CHj GdWjH s)
(3ChdgG (B:s
(3GdMeO ddg eMb GdMb bGd ehdGfG hHYO aEfi deG JUaMJ cJGH Jfjd GdGPcGQ bhdg GYde Cf GdYde gh MUhd UMhI GdTF ai GdYbd s
(3BNQgG (B:s
(3gPG BNQ eZGdWGJg hfSHI Cf YQV UGMH GdcJGH ai JCdja gPg GdeZGdWGJ hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs